2024
DOI: 10.3389/fpsyt.2023.1281268
|View full text |Cite|
|
Sign up to set email alerts
|

A systematic review and meta-analysis of neuroticism and anxiety during the COVID-19 pandemic

Khishigsuren Zuunnast,
Enkhtuvshin Regzedmaa,
Mandukhai Ganbat
et al.

Abstract: IntroductionIn response to the global impact of the COVID-19 pandemic, concerns about mental health, particularly anxiety levels, have become prominent. This study aims to explore the relationship between neuroticism, a personality trait associated with emotional instability, and anxiety during the COVID-19 outbreak.MethodsA comprehensive literature search was conducted using the Cochrane Library, HINARI, Google Scholar, and PUBMED, resulting in the identification of 26 relevant papers. The study protocol has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…The results indicate that negative emotionality was strongly associated with both perceived stress and life satisfaction. This agrees with multiple studies which suggest that negative emotionality is the most important predictor of perceived stress and life satisfaction (e.g., Anglim & Horwood, 2021;Bellingtier et al, 2023;Ikizer et al, 2022;Krautter et al, 2022;Liu et al, 2021;Ng & Kang, 2022;Rettew et al, 2021;Shokrkon & Nicoladis, 2021; see also Regzedmaa et al, 2024). Negative emotionality is a personality trait manifested by the tendency to experience anxiety, fear, and sadness.…”
Section: Perceived Stresssupporting
confidence: 91%
See 1 more Smart Citation
“…The results indicate that negative emotionality was strongly associated with both perceived stress and life satisfaction. This agrees with multiple studies which suggest that negative emotionality is the most important predictor of perceived stress and life satisfaction (e.g., Anglim & Horwood, 2021;Bellingtier et al, 2023;Ikizer et al, 2022;Krautter et al, 2022;Liu et al, 2021;Ng & Kang, 2022;Rettew et al, 2021;Shokrkon & Nicoladis, 2021; see also Regzedmaa et al, 2024). Negative emotionality is a personality trait manifested by the tendency to experience anxiety, fear, and sadness.…”
Section: Perceived Stresssupporting
confidence: 91%
“…These effects were found to persist to a certain level during the COVID-19 pandemic. It was found that especially high negative emotionality significantly increased perceived stress and decreased life satisfaction (e.g., Anglim & Horwood, 2021;Bellingtier et al, 2023;Ikizer et al, 2022;Krautter et al, 2022;Liu et al, 2021;Ng & Kang, 2022;Rettew et al, 2021;Shokrkon & Nicoladis, 2021; see also Regzedmaa et al, 2024). Hence, we assume that negative emotionality is positively associated with perceived stress [H1] and negatively with life satisfaction [H2].…”
Section: The Role Of Personality Traits and Self-efficacy In Stress P...mentioning
confidence: 99%